ANALISIS HARGA KAYU LAPIS TERHADAP NEGARA PESAING : Kasus Malaysia (A Price Analysis of Plywood on Competitor Country : Case of Malaysia - Rachman Effendi (Jurnal Penelitian Hasil Hutan, 1993)
Nowadays,  the role  of timber industry in Malaysia becomes more important. The rapid growth of timber industry can be illustrated by the increase  of the production  level of plywood and veneer. An annual increase of plywood production  since 1960 to 1988  was 1,519 %   The  increase  of plywood  production  is facing  a  number  of problems  such  as  decreasing in supply  of logs,  furher processing  of log is still undeveloped,  competition from  non wood materials such as steel,      concrete,  alumunium  and plastic,. Also price competition with  competitor countries such  as Indonesia and Philippine.   The objectives of this paper  is to study  the timber industry development,  especially  plywood industry and economic factors  which influenced Malaysia's plywood price where. a multiple regression analysis was used to analyze the plywood price.The results of the analysis shows that export price of plywood from  the competitor countries especially indonesia  and Philippines has influenced very significantly to the price fluctuation of Malaysia plywood.  It explained up to 88  % of the price fluctuations.  the remaining  12  %   is  explained  by some  other factors.   In  other  words,  the  competitions  price   is the  most prominant factor   in determining  the price fluctuation of Malaysian plywood.